Desenvolvimento de uma plataforma para monitoramento dos níveis de O2 disperso de rios componentes de uma microbacia de abastecimento de água usando microcontroladores programáveis - Sakiyama, Rubens Zenko (2019)
The development of urban and industrialized areas contributes to the increase of the amount of waste thrown into river beds. Due to the growing concern with preservation of the environment it makes necessary the develoment of tools to monitor conditions that leads to its degradation. Water quality assessment is commonly performed. However, in majority of cases, it is manually and locally. Therefore, several researchers have been engaged in the development of an online systems to surveil water quality. Considering that concentration of oxygen dissolved in water is one of the highest value parameter in water quality index, this work proposes the use of a wireless sensor network for monitoring dissolved oxygen concentration at three distinc locations in a water pump station at the Pirapó River, located in Maringá, Paraná state. The frequency of dissolved oxygen concentration and water temperature measurement values were defined by the difference between previous and current values. Dissolved oxygen concentration and water temperature were assessed and sent to a local data server where it was stored for online consultation and used to develop a database. Rainfall and solar radiation index were obtained from the Estação Meteorológica Principal de Maringá and analyzed altogether with dissolved oxygen concentration and water temperature.